Reflections on Challenges and Promises of Mixed-Initiative Interaction - Horvitz, Eric (2006)
Research on mixed-initiative interaction and assistance is still in its infancy but is poised to blossom into a wellspring of rich innovations that promises to change the way we work with computing systems—and the way that computing systems work with us. I share reflections about the opportunities ahead for developing computational systems with the ability to engage people in a deeply collaborative manner, founded on their ability to support fluid mixed-initiative problem solving.